Solving the climate crisis through social change [ public investment in social prosperity to cool a fevered planet - Lipow, Gar W. (New trends and ideas in American politics, 2012)
"Solving the Climate Crisis through Social Change - Public Investment in Social Prosperity to Cool a Fevered Planet"-- Provided by publisher